Model Antrian Pelayanan Terhadap Nasabah Bank BRI Menggunakan Petri Net dan Aljabar Max Plus - Nurdin, Sri Ayu; Yahya, Lailany; Hasan, Isran K; Nurwan, Nurwan (Scimadly Publishing, 2023)
Petri net is one model representing transitions and places connected by arrows. Max Plus Algebra is an algebraic structure in which all sets of real numbers are equipped with max (maximum) and (addition). This research created a Petri net model of the customer service system for Bank BRI and a Max Plus Algebra model related to time to minimize service time at Bank BRI. The result is periodic time or characteristic values and vector characteristics where the values and are . The value of this vector's characteristics becomes a periodic time, which only takes 2 days 3 hours during working hours to disburse money after the client's arrival.